A survey of ixodid tick species and molecular identification of tick-borne pathogens - Aktas, Munir (Elsevier, 2014)
This study was undertaken in two different climatic areas of Turkey to determine the presence of tick-borne pathogens of medical and veterinary importance. The ticks were removed from humans, pooled according to species and developmental stages, and analyzed by PCR, reverse line blot (RLB) and sequencing. Of the 2333 removed ticks from 10 species, 1238 (53.06%) were obtained from the arid cold zone, and the remaining 1095 (46.93%) were obtained from the humid zone. The removed ticks were identified as Hyalomma marginatum, Hyalomma detritum, Hyalomma excavatum, Rhipicephalus bursa, Rhipicephalus turanicus, Rhipicephalus sanguineus, Dermacentor marginatus, Haemaphysalis punctata, Haemaphysalis sulcata, Ixodes ricinus, Haemaphysalis and Ixodes spp. nymphs. The dominant species was L ricinus (61.27%) in the humid zone, whereas the Haemaphysalis spp. nymph dominated (30.29%) in the arid zone. Infection rates were calculated as the maximum likelihood estimation (MLE) with 95% confidence intervals (CI). Of the 169 pools tested, 49 (28.99%) were found to be infected with the pathogens, and the overall MLE of the infection rate was calculated as 2.44% (CI 1.88-3.17). The MLE of the infection varied among tick species, ranging from 0.85% (CI 0.23-2.34) in Haemaphysalis spp. nymph to 17.93% (CI 6.94-37.91) in D. marginatus. Pathogens identified in ticks included Theileria annulata, Babesia ovis, Babesia crassa, Anaplasma/Ehrlichia spp., Anaplasma ovis, Ehrlichia canis, Anaplasma phagocytophilum, Hepatozoon canis and Hepatozoon fells. Most tick pools were infected with a single pathogen. However, four pools infected with H. canis displayed infections with B. crassa, A. phagocytophilum and E. canis. The sequencing indicated that Anaplasma/Ehrlichia spp. was 100% identical to the sequence of Ehrlichia sp. Firat 2 and 3 previously identified from Hyalomma anatolicum. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Ixodid ticks; Tick-borne pathogens; PCR; RLB